2017
DOI: 10.1038/bjc.2017.369
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoural PD-L1 expression is associated with worse survival of patients with Epstein–Barr virus-associated gastric cancer

Abstract: Background:This study investigated the clinical relevance and prognostic impact of the overall expression of programmed cell death protein ligand-1 (PD-L1) and programmed cell death protein ligand-2 (PD-L2), in patients with Epstein–Barr virus-associated gastric cancer (EBVaGC).Methods:After reviewing 1318 consecutive cases of surgically resected or endoscopic submucosal dissected gastric cancers, the expression status of PD-L1 and PD-L2 in 120 patients with EBVaGC identified by EBV-encoded RNA in situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
2
43
0
1
Order By: Relevance
“…The programmed cell death protein1 (PD-1)-programmed death-ligand 1 (PD-L1) signalling pathway plays an important inhibitory role in the immune system, and its abnormal expression has been reported in a series of tumours, such as gastric cancer, non-small-cell lung carcinoma (NSCLC), and Hodgkin lymphoma. [4][5][6] PD-L1 has been considered to be a key factor in lymphocyte inhibition and immune response termination. 7 Studies have demonstrated that PD-L1 is up-regulated and results in a poorer prognosis in some types of cancer, including ovarian cancer, oesophageal cancer, and hepatocellular cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The programmed cell death protein1 (PD-1)-programmed death-ligand 1 (PD-L1) signalling pathway plays an important inhibitory role in the immune system, and its abnormal expression has been reported in a series of tumours, such as gastric cancer, non-small-cell lung carcinoma (NSCLC), and Hodgkin lymphoma. [4][5][6] PD-L1 has been considered to be a key factor in lymphocyte inhibition and immune response termination. 7 Studies have demonstrated that PD-L1 is up-regulated and results in a poorer prognosis in some types of cancer, including ovarian cancer, oesophageal cancer, and hepatocellular cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous EBVaGC-specific studies have focused on histomorphological characteristics, such as tumor-infiltrating lymphocyte (TIL) patterns [4] or expression of PD-L1 through immunohistochemistry (IHC) Raghav Sundar and Aditi Qamra have contributed equally and shared the first authorship. [5,6]. Large genomic studies of gastric cancer conducted by The Cancer Genome Atlas group (TCGA) [1] and the Asian Cancer Research Group (ACRG) [7] only include a small sample size of EBVaGC.…”
Section: Introductionmentioning
confidence: 99%
“…Однако требуется продолжение исследования. В целом роль экспрессии данного маркера в течении и прогнозе опухолевых заболеваний различных локализаций активно обсуждается в литературе [33][34][35], однако все сходятся во мнении, что при ВЭБ-ассоциированных неоплазмах экспрессия PD-L1 повышается [34,36]. Таким образом, по мере развития опухолевого процесса экспрессия факторов ангиогенеза увеличивается у этой категории больных.…”
Section: Discussionunclassified